Rate of growth of Pseudomonas fluorescens in donated blood. Issue 8 (August 1995) - Gibb, A P; Martin, K M; Davidson, G A; Walker, B; Murphy, W G
Abstract : AIMS--To examine how delayed refrigeration of blood affects the growth of Pseudomonas fluorescens, one of the two most important causes of sepsis resulting from transfusion of contaminated blood. METHODS--Two donations of whole blood were each divided into three aliquots and inoculated with 5-10 cfu/ml of a P fluorescens strain from a case of transfusion associated sepsis. From each donation, one aliquot was placed at 4 degrees C, one was held at 20 degrees C for six hours prior to refrigeration and the third was held at 20 degrees C for 24 hours prior to refrigeration. Samples were aseptically withdrawn over 17 days and bacterial counts were determined using a pour plate technique. RESULTS--The rate of growth of P fluorescens in blood at 20 degrees C was increased compared with blood at 4 degrees C. At 24 hours the aliquots held at 20 degrees C for six and 24 hours had, respectively, 174 and 29, 000 cfu/ml compared with 15 cfu/ml in aliquots held at 4 degrees C. There was no evidence of increased killing of P fluorescens at the higher temperature. CONCLUSIONS--These results suggest that blood for transfusion should be refrigerated as soon as possible after collection.